TINGKAT KESEJAHTERAAN PEMBUDIDAYA IKAN DALAM KOLAM DI KECAMATAN MALINAU KOTA KABUPATEN MALINAU KALIMANTAN UTARA - Onna Windah M (2339-1324, 2014)
The purposes of this study were to determine the welfare level of fishpond farmers in Malinau Kota Sub-district, Malinau District, North Kalimantan. The method used in the study was survey in which respondent interviews were done. The welfare analysis based on both the National Family Planning (BKKBN) and the NTP were used. The result showed that: (1) The percentage of the community grouped in the Keluarga Prasejahtera category was 25% followed by the Keluarga Sejahtera I group was 10%, and 50% was for the Keluarga Sejahtera III category. Meanwhile there were not the farmers welfare categorised either as Keluarga Sejahtera II and Keluarga Sejahtera III Plus; (2) The data analysis on Pond Farmers Term of Trade showed that the value was 4.60 and the total revenue of the pond farner enterprise was calculated for 8.42.